Application of edge computing in fault diagnosis of 10kV ring net switch cabinet. Issue 3 (April 2020) - Zhang, Zhengwen; Tian, Ersheng; He, Enping; Ma, Tao; Cheng, Yuhang
Abstract: To ensure the safe and reliable operation of the distribution network system, this paper analyzes the fault diagnosis of 10kV ring net switch cabinet, introduces the concept and advantages of edge computing, and then proposes a new fault diagnosis system of 10kV ring net switch cabinet based on edge computing. This paper also introduces the overall design of the system and the design of each part, and finally makes a contrastive analysis with the traditional fault diagnosis methods of the ring net switch cabinet.